Insulin-like Growth Factor-1 and Calcium Ion Levels are Negatively Associated with Serum β-Cross Laps in Multi-transfused β-thalassemia Major Patients - Sabar Widodo; Nyoman Suci Widyastiti; Edward Kurnia Setiawan Limijadi; Meita Hendrianingtyas; Dwi Retnoningrum; Ariosta Ariosta; Yetty Movieta Nency (The Indonesian Biomedical Journal, 2025)
BACKGROUND: Thalassemia patients with repeated transfusions (multi-transfusion) are often at risk of experiencing early osteoporosis. Several studies have demonstrated that osteoporosis in these individuals was associated with altered bone remodeling, characterized by decreased insulin-like growth factor-1 (IGF-1) and serum calcium ions, as well as increased serum β-Cross Laps (β-CTx) levels. Despite the prevalence of this condition, there is limited literature on the relationship between IGF-1 levels and calcium ions with β-CTx. Therefore, this study was conducted to examine the relationship between IGF-1 and calcium ions levels with serum β-CTx in multi-transfused β-thalassemia major patients.METHODS: A cross sectional study involved 29 thalassemia patients with multiple transfusions, aged 2-18 years, that were selected from the electronic medical records. Calcium ion levels were examined using ion selective electrode method. Subsequently, IGF-1 and serum β-CTx levels were examined by enzyme-linked immunosorbent assay (ELISA), and the data were analyzed using the Pearson correlation test.RESULTS: The results showed that the mean serum IGF-1 levels, calcium ion, and β-CTx were 20.11±20.763 ng/mL, 1.26±0.07 mmol/L, and 9330.40±1696.76 ng/mL, respectively. Statistical analysis showed a significant relationship between the levels of IGF-1 (r=-0.573; p=0.001) and calcium ion (r=-0.373; p=0.046) with serum β-CTx. A moderate negative relationship was found between IGF-1 levels and β-CTx, while calcium ion levels and β-CTx showed a weak negative relationship.CONCLUSION: A moderate negative correlation between IGF-1 and serum β-CTx, and a weak negative correlation between calcium ion and serum β-CTx suggest that IGF-1 and calcium ions may serve as potential indicators of bone turnover and osteoporosis risk in multi-transfused β-thalassemia major patients, underscoring their potential role in routine clinical evaluations.KEYWORDS: miR-200a expression, NO level, early-onset preeclampsia, late-onset preeclampsia